Markets and cooperation - Giancarlo Spagnolo (Fondazione Eni Enrico Mattei (FEEM), 1999)
Why do money and markets crowd out co-operative relations? This paper characterises the effects of intertemporal preferences, money, and markets on players' ability to co-operate in material-payoff supergames. Players' aversion to intertemporal substitution facilitates co-operation by decreasing their evaluation of short-run gains from deviations and increasing that of losses from punishments. Goods' markets and money may hinder co-operation by allowing players to reallocate short-run gains from deviations in time, at some cost. Allowing for free intertemporal reallocation of payoffs, perfect financial markets always make co-operation harder. Financial markets' imperfections facilitate co-operation by opposing this effect.
Keywords: C72; D51; O17; 330; Co-operation; repeated games; Prisoner's dilemma; commons; reciprocal exchange; implicit contracts; collusion; institutions; Marktmechanismus; Kooperation; Spieltheorie; Finanzmarkt; Theorie